Color specification of a single strand of yarn from a multispectral image. Issue 5 (6th July 2015) - Luo, Lin; Shen, Hui‐Liang; Shao, Si‐Jie; Xin, John H.
Abstract: Many applications in textile require color measurement of single strands of yarns due to unavailability of a mass of consecutive yarns. While multispectral imaging systems can capture images of single strands of yarns, an unavoidable problem accompanied is how to specify their colors from images, in which pixel values vary with positions owing to three‐dimensional shape of yarn. Based on the response of multispectral imaging systems to single strands of yarns, this article formulates the color specification problem as an optimization question and four methods are proposed: average of all pixels (AA), average of pixels in central area (AC), maxima of all pixels (MA), and lightness weighting method (LW). The first experiment analyzed color distribution of pixels on a single strand of yarn. Experimental results show pixels in central area have smallest color variation and largest intensity. The second experiment compared the proposed methods. Results show that CIEXYZ, L *, and C * values specified by the AA and MA methods are lowest and highest. Finally, colors of single strands of yarns specified by the proposed methods were compared with spectrophotometric colors of yarn windings using 12 pairs of single strands of yarns and yarn windings. Experimental results show the MA method yields the smallest lightness and chroma difference compared with spectrophotometric colors of yarn windings. The average color difference between spectrophotometric colors of yarn windings and multispectral imaging colors of single strands of yarns specified by the AA, AC, MA, and LW methods is 3.45, 2.72, 2.37, and 3.33 CMC(2:1) units. © 2015 Wiley Periodicals, Inc. Col Res Appl, 41, 500–512, 2016